The HpmA hemolysin is more common than HlyA among Proteus isolates. - Swihart, K G (1990)
Two different hemolysins, HpmA and HlyA, have been reported in Proteus spp. To study the distribution of these hemolysins among Proteus strains, isolates from various infections and normal feces were screened for hemolysin production. All 63 Proteus mirabilis strains and 23 of the 24 Proteus vulgaris strains produced a calcium-independent hemolytic activity detectable in cell-free supernatants. The calcium-independent activity was due to HpmA; this activity correlated with the presence of hpmA sequences and the production of an extracellular 166-kilodalton (kDa) protein that reacted with anti-HpmA antiserum. HpmA- mutants, constructed by deletion of the central portion of the hpmA gene, did not produce the 166-kDa protein and were no longer hemolytic when compared with their respective parent strains. Among the 87 P. mirabilis and P. vulgaris isolates examined, calcium-dependent hemolytic activity was produced by only two P. vulgaris strains. These strains produced a 110-kDa protein which comigrated with the Escherichia coli hemolysin (HlyA) antibodies in immunoblots. These studies show that Proteus spp. produce two distinct extracellular hemolysins, with nearly all strains producing the calcium-independent hemolysin, HpmA, but only an occasional P. vulgaris isolate producing HlyA.